Cover Feature: Elucidating Halogen‐Assisted Self‐Assembly Enhanced Mechanochromic Aggregation‐Induced Emission (ChemPhotoChem 7/2021). Issue 7 (26th June 2021) - Miao, Xinrui; Cai, Zhengkai; Li, Jinxing; Liu, Liqian; Wu, Juntian; Li, Bang; Ying, Lei; Silly, Fabien; Deng, Wenli; Cao, Yong
Abstract : The Cover Feature illustrates the halogen‐bonding‐induced, self‐assembly‐enhanced aggregation‐induced emission of a meta ‐bromide and phenyl‐ring‐substituted tetraphenylethene fluorophore. The molecular packing and intermolecular interactions are revealed by scanning tunneling microscopy (STM) at the molecular scale. More information can be found in the Communication by Xinrui Miao, Lei Ying, Fabien Silly, and co‐workers .